96.6k views
1 vote
-5 1/2 - 4 1/4 + 6 3/4
What is this ​

2 Answers

6 votes

Answer:


\large\boxed{-5(1)/(2)-4(1)/(4)+6(3)/(4)==-3}

Explanation:


-5(1)/(2)-4(1)/(4)+6(3)/(4)=-5(1)/(2)+\left(-4(1)/(4)\right)+6(3)/(4)\\\\\text{Use the Associative Property:}\ (a+b)+c=a+(b+c)\\\\=-5(1)/(2)+\left(-4(1)/(4)+6(3)/(4)\right)=-5(1)/(2)+\bigg((6-4)+\left((3)/(4)-(1)/(4)\right)\bigg)\\\\=-5(1)/(2)+\bigg(2+(3-1)/(4)\bigg)=-5(1)/(2)+2(2\!\!\!\!\diagup^1)/(4\!\!\!\!\diagup_2)=-5(1)/(2)+2(1)/(2)=-3

User Dabeiba
by
5.4k points
7 votes

Answer:

-3

Hope this helps :)

Have a great day !

5INGH

Explanation:


-5(1)/(2) - 4(1)/(4) +6(3)/(4) = -5(2)/(4) - 4(1)/(4) +6(3)/(4) = -9(3)/(4) +6(3)/(4) = -3

User RekrowYnapmoc
by
5.9k points